The Impact of Absenteeism in Banking Sector in Oman - Al Zadjali, Razan Saleh; Ibrahim, Omer Ali (International Review of Management and Marketing, 2021)
This work represents an attempt to identify the factors influencing absenteeism in banking sector in Oman. Primary quantitative data has been obtained via a structured closed-ended questionnaire, submitted to 150 employees of both genders and a variety of job responsibilities employed in the National Bank of Oman (NBO). This is based on current perceptions of likely causes as identified in the literature. Subsequent analyses have been carried out using the Pearson coefficient of correlation and Chi-square testing. The findings indicate that the workload and work pressure are the main contributing factors to employees' absenteeism. Other factors examined played a lesser role. Suggestions have been offered as to how to tackle absenteeism and its principal causes. Keywords: Absenteeism, Workload, Motivation, NBO, Oman JEL Classifications: M10, M50, M54 DOI: https://doi.org/10.32479/irmm.11245